2015
DOI: 10.1091/mbc.e15-05-0289
|View full text |Cite
|
Sign up to set email alerts
|

Axonemal dynein light chain-1 locates at the microtubule-binding domain of the γ heavy chain

Abstract: Dynein light chain 1 (LC1) of the outer arm dynein (OAD) complex associates with the microtubule-binding domain (MTBD) of γ heavy chain inside the complex. LC1 is considered to regulate the OAD activity and ciliary/flagellar motion by modulating γ MTBD's affinity to the B-tubule of the doublet microtubule in the axoneme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 49 publications
4
29
0
Order By: Relevance
“…One involving the central pair and radial spokes that impacts the inner arms, and second distinct system that activates the outer arms. This second system is thought to involve the highly conserved leucine-rich repeat protein LC1 (Benash- ski et al 1999;Wu et al 2000) that has recently been shown to bind the microtubule-binding domain of the g heavy chain (Ichikawa et al 2015). When mutant forms of this protein are expressed in a wild-type background, they yield dominant negative effects that have dramatic consequences on swimming velocity and on the ability of the cilia to maintain hydrodynamic coupling (Patel- King and King 2009;Rompolas et al 2010).…”
Section: Dynein Motor Function and Regulationmentioning
confidence: 99%
“…One involving the central pair and radial spokes that impacts the inner arms, and second distinct system that activates the outer arms. This second system is thought to involve the highly conserved leucine-rich repeat protein LC1 (Benash- ski et al 1999;Wu et al 2000) that has recently been shown to bind the microtubule-binding domain of the g heavy chain (Ichikawa et al 2015). When mutant forms of this protein are expressed in a wild-type background, they yield dominant negative effects that have dramatic consequences on swimming velocity and on the ability of the cilia to maintain hydrodynamic coupling (Patel- King and King 2009;Rompolas et al 2010).…”
Section: Dynein Motor Function and Regulationmentioning
confidence: 99%
“…Chemically modified gold nanoparticles visualize the tagged sites within protein complexes (Ichikawa et al, 2015;Guesdon et al, 2016;Song et al, 2014). Using gold nanoparticles with diameter less than 5 nm (Kitai et al 2011), the specific sites within ~30 nm CC1-protrusion (Figure 3, Figure 3-S1) and ~20 nm CC2-neck (Figure 4) were clearly discernible.…”
Section: Labeling Of Flexible Objects By Gold Nanoparticlesmentioning
confidence: 99%
“…Furthermore, it has been widely assumed that LC1 associates with AAA1 and AAA3 or AAA4 of the AAA+ ring in the gamma heavy chain of OAD (OADγ) in C. reinhardtii (Benashski et al 1999). However, it was recently reported that LC1 is tightly bound to the MTBD of OADγ, which is located at the tip of stalk region in the motor domain (Ichikawa et al 2015). This was the first report of an LC interacting with the MTBD.…”
Section: Light Chainmentioning
confidence: 92%
“…This was the first report of an LC interacting with the MTBD. Moreover, it was also discovered that the binding of LC1 to the MTBD decreases the MT-binding affinity of the HC (Ichikawa et al 2015). Because it has been reported that the ATPase activity of the HC is increased in the presence of MTs (Kon et al 2009), both results imply that LC1 indirectly changes the ATPase activity of OADγ and regulates ciliary/ flagellar beating.…”
Section: Light Chainmentioning
confidence: 95%